Immunomodulatory effect of a rodent bone marrow cytokine in improving antibody response in Newcastle disease vaccinated chicks - Ghosal, Debasis; Chakraborty, Dhruba; Chakraborty, Gopal; Chatterjee, Amaresh (The Indian Journal of Animal Sciences, 2012)
Outbreak of Newcastle disease (ND) in spite of vaccination is not infrequent in India. To abrogate this vaccine failure condition a nonspecies specific 12.7 kD immunomodulatory cytokine (BIM) is used. One drop of BIM (cone. 0.3 Âµg /25 Âµl) was applied via nasal or ocular route on 5th and 11 th day post R2B vaccination and antibody to ND virus was assayed after 2 and 6 weeks of vaccination. The mean antibody (Ab) titre at 2 weeks post-vaccination of control chicks was 1 in 517.7 while the vaccinated BIM treated group had a mean Ab titre of I in 1821 (P<0.001) indicating that the flock immunity of the BIM treated chicks with respect to R2B vaccination is more at 2 weeks compared to only vaccinated group. At 6 weeks both the groups have comparable Ab titre (control 1 in 2132, BIM 1 in 1898). BIM is heat stable which dispense the use of cold chain. This immunomodulatory role of BIM opens up a new cytokine based immunopotentiation in chicks.